First report of vancomycin-resistant Enterococcus faecalis in Uberaba, Minas Gerais state - Conceição,Natália (2010)
In this study we report the first isolation of VanA-type vancomycin-resistant Enterococcus faecalis strains from two different patients hospitalized in the same intensive care unit at the hospital of Universidade Federal do Triângulo Mineiro (UFTM), Uberaba, Minas Gerais, Brazil.